The Effect of Group Guidance with Sociodrama Techniques on Social Interaction - Kadek Ari Dwiarwati (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study aims to find out the Influence of Group Guidance With Sosiodrama Techniques on Social Interaction in Semester II Students of Undiksha Counseling Guidance Study Program. This research is a quantitative research analyzed using the T-test formula. The sample of this study was 60 students. Based on the results of the analysis obtained there is a significant influence of group guidance with sociodrama techniques on social interaction in students of semester II Of Counseling Guidance Study Program Undiksha. As well as the influence of group guidance with sociodrama techniques on social interaction in students of semester II Of Counseling Guidance Study Program Undiksha is 21.8% that is included in the low influence.